Rhodium-Catalyzed Direct Allylation of Simple Arenes by Using Gem-Difluorinated Cyclopropanes as Allyl Surrogates - Jiang, Zhong-Tao; Zeng, Yaxin; Xia, Ying (Synlett, 2021)
Gem-difluorinated cyclopropanes have become an important type of allyl surrogate in transition-metal-catalyzed ring-opening processes, as demonstrated recently through various important advances, especially with palladium catalysis. The versatile fluorinated allyl species generated in this way from gem-difluorinated cyclopropanes exhibit unique advantages compared with conventional allyl sources. By using gem-difluorinated cyclopropanes as allyl surrogates, we achieved a direct allylation of simple arenes through rhodium catalysis under mild conditions. This transformation permits directing-group-free allylation of simple arenes, including electron-neutral, electron-rich, and electron-deficient ones. Here, we give a brief introduction to this area and we discuss our thoughts regarding our recent work and its design.1 Introduction2 Our Design3 Condition Optimization and Substrate Scope4 Applications in Synthesis5 Mechanistic Discussions6 Conclusion and Outlook
Keywords: difluorocyclopropanes; transition-metal catalysis; allylation; C–C bond activation; rhodium catalysis; arenes